Chapter Un intervento sottotraccia. L’ospedale della Croce rossa italiana in Corea (1950-55) - POLSI, ALESSANDRO (Firenze University Press, 2025)
In the summer of 1950 the United States asked Italy for a military contribution, even symbolic, to be used in the war in Korea. The Italian government instead decided to send a humanitarian mission, as Sweden did, and sent a Red Cross field hospital. The mission, initially underfunded, encounters various problems until, to avoid a dangerous scandal, the government agreed to provide adequate means. After the armistice was signed, Italy decided to quickly withdraw the hospital, despite local requests to stay, showing little interest in developing a political and economic presence in the Far East.